Ion Beam Analysis for the Investigation of Diffusion Processes - Becker, H.-W. (HNPS Advances in Nuclear Physics, 2020)
The unique advantages of ion beam analysis, such as the depth resolved unam- biguous stoichometric information of RBS or the possibility to detect hydrogen with high depth resolution still opens new applications in fundamental as well as applied science. Two examples are presented here. The diffusion of hydrogen in cement during the formation of cement has been studied with the 15N hydrogen depth profiling. It could be shown, that the known stages of the hydration process are correlated with the diffusion of hydrogen on a nanometer scale. Diffusion processes play also an important role in geology. The investigation of such processes with RBS will be presented. Prospects of diffusion studies using isotopie tracing with low lying resonances will be discussed.